Beyond traditional trade unionism: innovative worker responses in three African cities. Issue 8 (17th November 2021) - Webster, Edward; Ludwig, Carmen; Masikane, Fikile; Spooner, Dave
ABSTRACT: Insufficient attention has been given to how workers organizations are challenging precarious work through new hybrid forms of organizing in the Global South. In this article we examine three examples where workers innovate and experiment with new forms of worker organization in three African cities. These include a traditional union reaching out to precarious workers in Cape Town, hybrid forms of worker organizations in Kampala, and workers in the gig economy starting a process of self-organization in Johannesburg. We argue that there is manifold experimentation taking place on the periphery of the labour movement and that the forms of organizations often differ from traditional unionism. Our comparisons reveal that if current trade union organizations are to meet the needs of informal workers and the new workers of the digital economy they will need to transform, rediscover their power and the capabilities necessary to realize this power.